The Long-Term Mental Health Consequences of Torture, Loss, and Insecurity: A Qualitative Study Among Survivors of Armed Conflict in the Dang District of Nepal - Kienzler, Hanna; Sapkota, Ram P. (Frontiers in Psychiatry, 2020)
Background and Objectives: Nepal has witnessed several periods of organized violence since its beginnings as a sovereign nation. Most recently, during the decade-long Maoist Conflict (1996–2006), armed forces used excessive violence, including torture, resulting in deaths and disappearances. Moreover, there is widespread gender-, ethnic- and caste-based discrimination, and grossly unequal distribution of wealth in the country. While the immediate mental health effects of the conflict are well studied, less is known about the long-term effects of the conflict. This article sets out to explain how Nepalese survivors of violence perceive their wellbeing and mental health, search for help and construct their health care pathways and therapeutic itineraries. The aim is to provide a better understanding of local explanatory models and healthcare behaviors. Methods: Semi-structured interviews were carried out with 25 people (14 men, 11 women) aged 30 to 65 in Dang district in 2013. To elicit illness narratives, a translated and culturally adapted version of the McGill Illness Narrative Interview (MINI) was used. Additionally, participants were interviewed about their war experiences and present-day economic and social situations. The transcripts were coded using deductive and inductive approaches and analyzed through thematic analysis. Results: The study provides insight into temporal narratives of illness experience and explanatory modules. Symptoms were found to be widespread and varied, and were not solely attributed to violent experiences and memories, but also to everyday stressors related to survivors’ economic, social, and familial situations. In terms of help- and health-seeking behavior it was found that participants resorted to various coping strategies such as social activities, avoidance, withdrawal, and substance use. Many participants had received biomedical treatment for their psychosocial problems from doctors and specialists working in public and private sector clinics and hospitals as well as different forms of traditional healing. Conclusions: These results shed light on the long-term impact of the Nepalese conflict on survivors of extreme violence, highlighting local explanatory models and help- and health-seeking behaviors. These findings inspire recommendations for the development of context specific and holistic psychosocial interventions focusing on well-being, social determinants of health, and human rights.